Trends of syngas as a fuel in internal combustion engines - Hagos, F.Y. (2014)
Syngas from biomass and solid waste is a carbon-neutral fuel believed to be a promising fuel for future engines. It was widely used for spark-ignition engines in the WWII era before being replaced with gasoline. In this paper, the technological development, success, and challenges for application of syngas in power generating plants, the trends of engine technologies, and the potential of this fuel in the current engine technology are highlighted. Products of gasification vary with the variation of input parameters. Therefore, three different syngases selected from the two major gasification product categories are used as case studies. Their fuel properties are compared to those of CNG and hydrogen and the effects on the performance and emissions are studied. Syngases have very low stoichiometric air-fuel ratio; as a result they are not suitable for stoichiometric application. Besides, syngases have higher laminar flame speed as compared to CNG. Therefore, stratification under lean operation should be used in order to keep their performance and emissions of NOx comparable to CNG counterpart. However, late injection stratification leads to injection duration limitation leading to restriction of output power and torque. Therefore, proper optimization of major engine variables should be done in the current engine technology. Â© 2014 Ftwi Yohaness Hagos et al.